Role of smart specialisation in financing the development of regions in perspective 2020 - Gulc, Aleksandra (Business, Management and Economics Engineering, 2015)
The aim of this article is to present the role of smart specialization concept in the process of providing funds for regional development. The systematic literature review was conducted in order to identify the role of smart specialisation concept in the process of providing funds for regional development. The methodology followed for the literature review included two main phases: selection and analysis. The article presents: (i) the idea of smart specialisation, (ii) characteristics of the areas of specialisation in the European Union, (iii) the creation of smart specialization strategies in the regions, (iv) the role of smart specialization in financing the development of regions, (v) examples of methodological approaches to identify smart specialisation at the regional level. The research examines the relationship between smart specialisation and process of providing funds for regional development.